Three dimensional imaging based on ultrasonic linear phased array probe - Changli Sun; Tie Gang; Changxi Wang; Jinghong Yang; Xinmeng Zhang; Changqing Xia; Zhanqi Yan; Yan Jiang (2014 IEEE Far East Forum on Nondestructive Evaluation/Testing, 2014)
3D ultrasound has got considerable development in medicine, but in the field of non-destructive testing of industry still lags behind. Three-dimensional ultrasound images can visually display spatial distribution of defects, make the test results easier to be understood and evaluated. This paper presented a 3D imaging method, which using linear phased array probe detection system to collect scan data, and then 3D reconstruction it on Matlab platform, realized three-dimensional visualization of artificial defects. Testing personnel can observe the spatial distribution of defects directly without analysis such two-dimensional images as sector scan, B-scan and C-scan frame by frame.